Wind Power Variability and Singular Events - Martin-Martínez, Sergio; Vigueras-Rodríguez, Antonio; Gómez-Lázaro, Emilio; Molina-García, Angel; Muljadi, Eduard; Milligan, Michael (IntechOpen, 2012)
None